Contributing Factors of Anxiety on Healthcare Workers during COVID-19 Pandemic at Referral Hospital of Sumatra Region in Indonesia - Christine Raphaela Tiarmauli Simanjuntak; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Elmeida Effendy; Fotarisman Zaluchu (Public Health of Indonesia)
Background:During the Coronavirus Disease 2019 (COVID-19) pandemic, nurses and doctors served as the frontline healthcare workers. Consequently, mental health issues among healthcare workers can develop into significant health problems and impose a substantial social burden, particularly on nurses and doctors working in hospital settings.